Upaya Meningkatkan Hasil Belajar Siswa dalam Pembelajaran Matematika pada Konsep Bangun Ruang Sisi Datar melalui Pendekatan CTL (Contextual Teaching and Learning) - Sudarwati, Eny (Attractive : Innovative Education Journal, 2024)
The Efforts to improve student learning outcomes in mathematics learning, especially in the concept of flat-sided shapes, using the CTL (Contextual Teaching and Learning) approach at SMP Negeri 2 Telukjambe Barat. The CTL approach usually emphasizes active involvement of students in the learning process by relating learning material to real contexts or student experiences. The research aims to improve students' understanding and skills in understanding the concept of flat-sided geometric figures through the CTL approach. This can be done by strengthening the connection between the mathematical material being taught and the situation or context around students, so that they can more easily understand and apply these concepts in everyday life. This research is very relevant and useful because it helps increase the effectiveness of mathematics learning and expands students' understanding of mathematical concepts that may seem abstract to them. Thus, the results are expected to provide better insight into how the CTL approach can improve student learning outcomes in the context of mathematics learning. Keywords: Learning Outcome, Contextual Teaching and Learning